Enhanced Antibody Responses in a Novel NOG Transgenic Mouse with Restored Lymph Node Organogenesis - Takahashi, Takeshi; Katano, Ikumi; Ito, Ryoji; Goto, Motohito; Abe, Hayato; Mizuno, Seiya; Kawai, Kenji; Sugiyama, Fumihiro; Ito, Mamoru (Frontiers in Immunology, 2018)
Lymph nodes (LNs) are at the center of adaptive immune responses. Various exogenous substances are transported into LNs and a series of immune responses ensue after recognition by antigen specific lymphocytes. Although humanized mice have been used to reconstitute the human immune system, most lack LNs due to deficiency of the interleukin (IL)-2Rg gene (cytokine common g chain, gc). In this study, we established a transgenic strain, NOG-pRORgt-gc, in the NOD/shi-scid-IL-2Rgnull (NOG) background, in which the gc gene was expressed in a lymph-tissue inducer (LTi) lineage by the endogenous promoter of RORgt. In this strain, LN organogenesis was normalized and the number of human T cells substantially increased in the periphery after reconstitution of the human immune system by human hematopoietic stem cell transplantation. The distribution of human T cells differed between NOG-pRORgt-gc Tg and NOG-non Tg mice. About 40% of human T cells resided in LNs, primarily the mesenteric LNs. The LN-complemented humanized mice exhibited antigen-specific IgG responses together and an increased number of IL-21+–producing CD4+ T cells in LNs. This novel mouse strain will facilitate recapitulation of human immune responses.